Towards Efficient and Secure Geographic Routing Protocol for Hostile Wireless Sensor Networks. (4th August 2013) - Lyu, Chen; Gu, Dawu; Zhang, Yuanyuan; Lin, Tingting; Zhang, Xiaomei
Traditional routing protocols are quite vulnerable under the attacks from both external and internal attackers. In this work, we examine the impact of a wide variety of attacks in malicious wireless sensor networks scenario. An Efficient and Secure Geographic Routing protocol ESGR is proposed to exploit the geographic location, cryptography mechanisms, and broadcast nature of the wireless channel. ESGR utilizes the geographic leashes and the TESLA scheme to provide resistance against the Sybil attack and wormhole attack. Meanwhile, it employs a distributed trust model and the packets opportunistic forwarding to prevent black hole and gray hole attacks. We demonstrate the results through analysis and simulations that ESGR effectively mitigates a specific variety of attacks and ensures high packet delivery rate in malicious sensor network environment.